PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry (The Accounting Review, 1940)
Abstract The article presents problems that were presented by the American Institute of Accountants on May 16, 1940, as the first half of the examination in accounting theory and practice. Candidates were required to solve all problems in six hours. The following weights were assigned, problem 1, 10 points; problem 2, 15 points; problem 3, 20 points; problem 4, 20 points; problem 5, 35 points.